The Positive Effects of Trait Emotional Intelligence during a Performance Review Discussion – A Psychophysiological Study - Salminen, Mikko; Ravaja, Niklas (Frontiers in Psychology, 2017)
Performance review discussions of real manager - subordinate pairs were examined in two studies to investigate the effects of trait emotional intelligence (EI) on dyad member’s felt and expressed emotions. Altogether there were 84 managers and 122 subordinates in two studies using 360 measured and self-reported trait EI. Facial electromyography, and frontal EEG asymmetry were collected continuously. Manager’s high trait EI was related to increased positive valence emotional facial expressions in the dyad during the discussions. The managers also had more EEG frontal asymmetry indicating approach motivation, than the subordinates. In addition, actor and partner effects and actor × partner interactions, and interactions between the role and actor or partner effect of trait EI were observed. Both actor and partner trait EI were related to more positive self-reported emotional valence. The results imply that trait emotional intelligence has a role in organizational social interaction.